2011
DOI: 10.1007/978-3-642-19641-6_10
|View full text |Cite
|
Sign up to set email alerts
|

Giga-Scale Multiresolution Volume Rendering on Distributed Display Clusters

Abstract: Abstract.Visualizing the enormous level of detail comprised in many of today's data sets is a challenging task and demands special processing techniques as well as a presentation on appropriate display devices. Desktop computers and laptops are often not suited for this task because data sets are simply too large and the limited screen size of these devices prevents users from perceiving the entire data set and severely restricts collaboration. Large high-resolution displays that combine the images of multiple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 33 publications
(32 reference statements)
0
4
0
Order By: Relevance
“…This allows researchers to build tiled displays out of commodity off-the-shelf computers [25]. Thelen et al [35] demonstrated a tiled display wall composed out of 50 LCD panels that are driven by 25 computers used for large-scale volume visualization. Renambot et al [29] introduced a scalable environment that can utilize tiled display configurations to provide a virtual highresolution framebuffer to an application program.…”
Section: Related Workmentioning
confidence: 99%
“…This allows researchers to build tiled displays out of commodity off-the-shelf computers [25]. Thelen et al [35] demonstrated a tiled display wall composed out of 50 LCD panels that are driven by 25 computers used for large-scale volume visualization. Renambot et al [29] introduced a scalable environment that can utilize tiled display configurations to provide a virtual highresolution framebuffer to an application program.…”
Section: Related Workmentioning
confidence: 99%
“…(Paper Isa) JD Multiresolution techniques [29,32,3] use special data structures such as octrees [5,17,10], N 3 -trees [6], wavelets [11], 3D mipmaps, hierarchical grids [8], or other sparse representations [26,33], in some cases also combined with compression techniques [9,7] and streaming [28]. We will concentrate on regular representations, as they are the most commonly found in commercial software.…”
Section: Previous Workmentioning
confidence: 99%
“…This allows researchers to build tiled displays out of commodity off-the-shelf computers (Nirnimesh et al [2007]). Thelen et al [2009] demonstrated a tiled display wall composed out of 50 LCD panels that are driven by 25 computers used for large-scale volume visualization. Renambot et al [2004] introduced a scalable environment that can utilize tiled display configurations to provide a virtual high-resolution framebuffer to an application program.…”
Section: Related Workmentioning
confidence: 99%